Pastoral Power Beyond Psychology's Marginalization Resisting the Discourses of the Psy-Complex - Helsel, Philip Browning. (New Approaches to Religion and Power, 2015)
This book explores the suffering of social class and how traditional biomedical models for mental illness do not adequately account for the stresses of poverty. Turning to mental health user testimonies, this book equips ministers and counsellors to become working class advocates.